Rapid progress for non-nuclear estrogen receptor signaling - Mendelsohn, Michael E. (American Society for Clinical Investigation, 2010)
Estrogen receptors are best known as ligand-activated transcription factors that regulate vascular cell gene expression. For many years now, a rapid signaling pathway mediated by cell membrane–associated estrogen receptors also has been recognized, but the physiological relevance of this pathway has remained unclear. In this issue of the JCI, Chambliss et al. provide new data to indicate that activation of non-nuclear estrogen receptor signaling regulates processes central to cardiovascular health and disease. These investigators show that an estrogen-dendrimer conjugate (EDC), which activates estrogen receptors but remains non-nuclear, stimulates vascular EC migration in vitro and protects against vascular injury in vivo. They show further that the vascular benefits of EDC in vivo occur selectively in the vasculature, without stimulating the uterus or enhancing growth of breast cancer xenografts. Taken together, these findings indicate that activation of non-nuclear estrogen receptor signaling regulates vascular events of physiological relevance and suggest that translation of these findings into clinically relevant therapeutic interventions is a logical next goal.